Fictions that save: Migrants' performance and Basotho national culture - Coplan, David (My University, 1991)
Of all South Africa's neighbors, none has suffered more severely from expropriation and underdevelopment by white colonialism and supremacy than the Kingdom of Lesotho. In reality, Lesotho is not South Africa's neighbor but its backlot: an eroded, mountainous, Belgium-sized (11,716 sq. mi.) remnant of a once expansive semi-feudal African highveld state. The military depredations of the Free State Afrikaners, combined with successive betrayals by its erstwhile "protectors," the imperial British, transformed Basutoland from a largely self-sufficient agricultural exporter to an impoverished, dependent supplier of labor to South Africa (Murray 1980). While independence from Britain in 1966 did nothing to improve its economic position, Lesotho is one African nation whose citizens have never felt the slightest nostalgia for the colonial period. In the mid-19th century, the Basotho (sing.: Mosotho) were lauded by missionaries and resident British officials for their courtliness, ingenuous adaptibility, and eagerness for the "progress" they believed would come from the adoption of European ways. In the event, however, British and white settler colonialism deprived them of both autonomy and resources in virtually every sphere... Among the various categories of Basotho performers and performances, this paper focuses on migrant tavern singers turned recording artists, to whom some of the task of making and remaking Basotho "national culture" has fallen. Their songs, long performed in wayside bars and now widely distributed on radio and audio cassette, reveal the dynamics of genre, gender, and expressive authority in the politics of performance. Their relation to Sesotho as emergent tradition embodies the layered contradictions created by the need for social solidarity in the face of competing positions and interests, and for historical continuity (represented in collective metaphors in the face of a radically transformed and fragmented social reality (Marcus and Fischer 1986:184-5). In proposing the universality of the marginal as the defining condition and not merely the by-product of structuration, Babcock-Abrahams argues that marginality is not a structurally residual category, but "That which is socially peripheral or marginal is symbolically central and predominant" (Babcock-Abrahams 1975:155). Recognizing this, performers openly adopt "marginality" as a stance from which to address the tension between the impracticabilities of solidary structural ideals and the conflictual structure of real social practices.
African Studies Seminar series. Paper presented March, 1991
Keywords: Sotho (African people); Ethnology. Lesotho; Culture. Lesotho